Desisting into what?: an exploration of desistance from crime after imprisonment among Chilean women - Droppelmann, Catalina (Geographies of gendered punishment, 2024)
While prison reentry is a complex process, linked to several contextual factors, its success or failure has traditionally been measured based on recidivism outcomes (Durose et al., 2014). The present chapter analyzes the process of reentry among a group of Chilean women through the critical lens of gender. We first describe methodological aspects of the study and its participants. Then, we analyze the beginnings of the reentry process, focusing on the structural obstacles to social integration, which are associated with the fulfillment of gender roles and the occurrence of multiple demands. We then discuss the participants’ identity changes after leaving prison. The results raise the question of the extent to which women have the opportunity to rewrite their past, given the structural constraints of gender and class; therefore, we explore the obstacles they encounter after imprisonment and how they perceive their ability to leave crime behind. Finally, we describe how the participants developed a normative life script, based on a notion of redemption that is anchored in traditional gender roles and the ethics of care.